The psychosocial outcomes of individuals with hematological cancers: Are we doing enough high quality research, and what is it telling us?. (May 2016) - Bryant, Jamie; Mansfield, Elise; Hall, Alix; Waller, Amy; Boyes, Allison; Jayakody, Amanda; Dodd, Natalie; Sanson-Fisher, Rob
Highlights: The number of publications examining psychosocial outcomes among hematological caner patients increased 8.8% each year. Most studies examining psychosocial outcomes among hematological cancer patients are descriptive. Only two of ten intervention studies were successful in improving patients psychosocial outcomes. Abstract: This systematic review assessed the quantity and quality of research examining the psychosocial outcomes among hematological cancer patients. Studies were categorised as either measurement, descriptive or intervention. Intervention studies were further assessed according to Effective Practice and Organisation of Care (EPOC) methodological criteria. A total of 261 eligible papers were identified. The number of publications increased by 8.8% each year (95% CI = 7.5–10.2%; p < 0.0001). The majority of studies were descriptive (n = 232; 89%), with few measurement (n = 8; 3%) and intervention (n = 21; 8%) studies identified. Ten intervention studies met EPOC design criteria, however only two interventions, one targeted at individuals with Hodgkin's or Non-Hodgkin's lymphoma and one targeted at individuals with leukaemia, lymphoma or myelomatosis were successful in improving patients' psychosocial outcomes. Despite an increasing volume of research examining psychosocial outcomes of hematological cancer patients, there is a need for robust measurement and methodologically rigorous intervention research in this area.